Cyber laws intellectual property and E-Commerce security - Krishna Kumar (Ed.); Sharma, s R (Ed.) (New Delhi Dominant Publisher and Distributors, 2001)
The present publication examines in detail the legalities of safeguard against cyber crime and provide a useful profile of the technology and counter technology to give effect to cyber laws.It is of great significance that India is one ofthe first countri
Keywords: Electronic commerce-Laws and legislation; Commercial law; Intellectual property; Copyright